ANALISA EFEKTIVITAS BRIDGING SYSTEM ANTARA SIPD-BLUD DENGAN CMS-BANK JATENG PADA TRANSAKSI PEMBAYARAN BELANJA BLUD RSUD BENDAN KOTA PEKALONGAN - Yohani Yohani; Muhammad Fithrayudi Triatmaja; Novianita Novianita (Neraca, 2026)
The rapid advancement of information technology today enables institutions to develop information systems to support their operational activities. Since 2021, RSUD Bendan Kota Pekalongan has implemented SIPD BLUD (Local Government Information System for Regional Public Service Agencies) for financial management, including the recording of hospital revenues, cash expenditures, and accounts payable. Meanwhile, to process BLUD expenditure payments, RSUD Bendan utilizes the CMS Bank Jateng (Cash Management System), an internet banking application specifically designed for regional government organizations (OPD). This article aims to analyze the effectiveness of the bridging system between SIPD BLUD and CMS Bank Jateng in facilitating BLUD expenditure payment transactions at RSUD Bendan. This study employs a qualitative descriptive research methodology, relying on primary data obtained through interviews and direct observation. To enhance data validity, methodological triangulation was applied by comparing the results of interviews with observations. The findings indicate that the bridging system between SIPD BLUD and CMS Bank Jateng functions as expected and is effective, as evidenced by the successful disbursement of BLUD payments from RSUD Bendan to vendors in accordance with the information provided in the SPD (Disbursement Order Letter) issued by the SIPD BLUD application.   Referensi Arifah, F. N. (2023). Konsep sistem informasi: Teori dan konsep. Yayasan Literasi Sains Indonesia. BLUD.co.id. (n.d.). Implementasi teknologi “bridging system”. https://blud.co.id/ Habiby, M. (2025). Pengaruh sistem otorisasi dan sistem informasi akuntansi terhadap efektivitas sistem pengendalian internal klien di Kantor Akuntan Publik Boy Febrian. Sainmikum, 2(2), 96–102. Martin, E. W., Brown, C. V., DeHayes, D. W., Hoffer, J. A., & Perkins, W. C. (2002). Managing information technology (4th ed.). Prentice Hall. Moleong, L. J. (2014). Teknik analisis data. PT Remaja Rosdakarya. Menteri Dalam Negeri Republik Indonesia. (2018). Peraturan Menteri Dalam Negeri Nomor 79 Tahun 2018 tentang Badan Layanan Umum Daerah. https://peraturan.bpk.go.id/ Nadiva, N., & Safriantini, D. (2024, Desember). Digitalisasi keuangan: Efektivitas sistem informasi akuntansi penerimaan kas di kasir induk Rumah Sakit Umum Daerah dr. H. Abdul Moeloek Provinsi Lampung. An-Nadaa: Jurnal Kesehatan Masyarakat, 11(2), 102–109. Pemerintah Republik Indonesia. (2019). Peraturan Pemerintah Republik Indonesia Nomor 12 Tahun 2019 tentang Pengelolaan Keuangan Daerah Pasal 1 angka 58. https://peraturan.bpk.go.id/ Pratama, R. A., Silalahi, A. D., & Saraswati, D. (2021, Desember). Analisis sistem informasi akuntansi penerimaan dan pengeluaran kas untuk perencanaan dan pengendalian keuangan pada Rumah Sakit Mitra Sejati Presiden Republik Indonesia. (2018). Peraturan Presiden Republik Indonesia Nomor 95 Tahun 2018 tentang Sistem Pemerintahan Berbasis Elektronik (SPBE) Pasal 7. https://peraturan.bpk.go.id/ Presiden Republik Indonesia. (2018). Peraturan Presiden Republik Indonesia Nomor 54 Tahun 2018 tentang Strategi Nasional Pencegahan Korupsi (STRANAS-PK). https://peraturan.bpk.go.id/ Santosa, B. (2020). Pedoman pengelolaan keuangan Badan Layanan Umum Daerah.